EVALUATION OF THE EFFECT OF CLAY MINERAL CHARACTERISTICS ON THE SLOPE STABILITY UNDER THE SPILLWAY STRUCTURE OF TUGU DAM, TRENGGALEK REGENCY, EAST JAVA - Iqbal Hamidi, Muhammad
History records that dams collapses occurred due to slope instability which was influenced by local geological conditions. Several types of mineral clay have physical and mechanical properties that affect slope stability, such as having a low value of shear strength and a high value of soil shrinkage. The purpose of this research is to evaluate the swelling and shear strength analysis of mineral clay and to relate it to X-ray diffraction analysis or XRD. In determining the value of shear strength obtained from the results of direct shear tests, while the value of swelling and shrinkage pressure is obtained from the results of the swelling test. To strengthen the engineering judgment of clay mineral characteristics, in this study an analysis was carried out using the XRD method which is an effective analytical method in describing minerals and certain chemical compounds in solid form using x-ray diffraction. XRD testing on clay minerals has several test conditions, such as air dried, ethylene glycolated, and heated. Based on the results of XRD analysis on the sample LP-2 which represents the colluvial layer, several peaks were obtained in the air dried or AD condition, namely at 7.4 Å, 4.3 Å, and 3.4 Å. In the condition of ethylene glycolated or EG only has a peak with a value of 3.4 . For the heated conditions of 500°C, did not find a peak in the sample. Based on these data, the clay minerals contained in colluvial are haloysite, kaolin, and smectite groups. The results of XRD analysis on the LP-3 sample which represents the sandy silt layer, obtained several peaks in AD conditions, namely at 14.9 Å, 7.3 Å, and 4.3 Å. In the EG conditions, peaks at 7.3 Å, 4.3 Å, and 3.3 Å. For heated conditions 500°C, there is no peak. Based on these data, the clay minerals contained in the sandy silt are chlorite, kaolin, and smectite groups. Based on the results of the swelling analysis on the LP-2 sample which is representative of colluvial with a clay grain size content of 20%, a pressure of 0.04 kg/cm² or 0.39 Ton/m² with this value can be included in the classification of low expansive potential. In the results of the swelling test analysis on the LP-3 sample which represents a layer of sandy silt with a clay grain size content of 58%, a pressure of 0.04 kg/cm² or 0.39 Ton/m² with this value can be included in the classification of low expansive potential. From the value of swelling pressure on colluvial lithology and sandy silt, it does not have an uplift effect on the spillway structure because the resulting pressure is smaller than the spillway load. Based on the results of direct shear strength on undisturbed surface samples, colluvial lithology has a cohesion value of 2.55 Ton/m2 and an internal shear angle of 22°, while sandy silt lithology has a cohesion value of 2.85 Ton/m2 and an internal shear angle by 20°. The results of direct shear strength on the residual condition sample, obtained colluvial lithology has a cohesion value of 1.55 Ton/m2 and an internal shear angle of 15°, while the sandy silt lithology has a cohesion value of 1.60 Ton/m2 and an internal shear angle of 12 °. The slope stability modeling of the spillway is carried out using the limit equilibrium method which is expressed in the value of the safety factor. From the results of slope stability modeling in static conditions without the presence of a phreatic line, the safety number is 1.57>1.50 (safe). Modeling with static conditions in the presence of a phreatic line produces a safety factor of 1.36<1.50 (not safe). Slope modeling with seismic conditions is done by adding a pseudostatic earthquake load parameter with a return period of 2500 years, the Kh value is 0.236. From the modeling results, the value of the safety factor is reduced by 0.67<1.10 (unsafe). In slope stability modeling using residual parameters, the value of the safety factor without the phreatic line is 1.25<1.50 (unsafe), modeling by adding the phreatic line, the safety factor value is 1.08<1.50 (unsafe), and the modeling was continued by adding a pseudostatic earthquake load to obtained a safety factor value of 0.53<1.10 (unsafe). Sensitivity analysis was carried out on the parameters of density, cohesion, and shear angle of colluvial lithology and sandy silt to the slope safety factor. Sensitivity analysis was also carried out on changes in ground water level and its effect on the slope safety factor. Based on the results of sensitivity analysis, colluvial lithology has a density parameter that affects slope stability, while in sandy silt it has an internal shear angle parameter that can affect slope stability. The results of the sensitivity analysis to changes in the rising ground water level also show a change in the value of the safety factor which is decreasing significantly.